Memória ambiental, cultural e turismo no vale histórico do Rio Paraíba do Sul: design de uma pesquisa - Whitaker, Valéria; Whitaker, Dulce Consuelo Andreatta [UNESP]; Souza, Marinaldo Fernando de [UNESP]; Pereira, Márcia Izabel do Vale (My University, 2011)
This text is aimed at disseminating cultural and environmental wealth of a region little known of major tour operators - which is strongly marked by historical traditions, in a bucolic rural still and by the hospitality of its residents. The Historic Valley of Rio Paraíba do Sul, although located in the Rio - Sao Paulo road lives in the shadow of the remarkable progress of the industrial cities in the main Valley. This paper presents results of research that deepened the knowledge of this region, with notable findings from the standpoint of culture and tourism, regional and national history. Isolated by considerable geographical barriers, this region has two aspects: the rebirth of nature after the decline of coffee plantations, with ecological sanctuaries that can now point toward environmental sustainability, and the formation of a culture with two historical times - refinement inherited from the barons coffee, paradoxically linked to the rustic countryside and modernity derived of its proximity to major centers. The results presented here are part of exploratory research, but were presented at different events, emphasizing the baroque character of practices derived from these two historical times and tourist potential related to the “cultura tropeira” and to hospitality that marks this countryside.

Este texto tem como objetivo divulgar a riqueza cultural e ambiental de uma região pouco conhecida dos grandes circuitos turísticos – marcada fortemente por tradições históricas, por um rural ainda bucólico e pela hospitalidade dos seus moradores. O Vale Histórico do Rio Paraíba do Sul, embora situado no eixo Rio-São Paulo, vive à sombra do notável progresso das cidades industrializadas do Vale principal. Este texto apresenta resultados de uma pesquisa que aprofundou o conhecimento dessa região, com achados do ponto de vista da cultura, da História Regional, Nacional e do Turismo. Isolada por barreiras geográficas consideráveis, essa região apresenta dois aspectos: o renascimento da natureza após a decadência do café, com santuários ecológicos que hoje podem apontar na direção da sustentabilidade ambiental; e a formação de uma cultura com dois tempos históricos – refinamento herdado dos barões do café, paradoxalmente ligado à rusticidade do rural e à modernidade derivada da sua proximidade com os grandes centros. Os resultados aqui descritos são parte de pesquisa ainda exploratória, mas já foram apresentados em diferentes eventos, enfatizando o caráter barroco das práticas, derivado desses dois tempos históricos e as potencialidades turísticas ligadas à hospitalidade da cultura tropeira que marca o seu rural.
Memory environment, tourism and cultural history in the valley of Paraíba do Sul river: a research design
Keywords: Memory; Environment; Culture; Tourism; Valley Historical Rio Paraíba do Sul; Memória; Ambiente; Cultura; Turismo; Vale Histórico do Rio Paraíba do Sul